2023
DOI: 10.3390/microorganisms11102423
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Potential Molecular Mechanisms of Individual Growth and Rumen Development in Calves with Different Feeding Patterns

Jie Wang,
Kaisen Zhao,
Mianying Li
et al.

Abstract: At present, it is common to feed calves with “Concentrate”, “Concentrate + hay” and TMR “Total Mixed Rations” feeding patterns in China, which achieved well feeding efficiency, but the three feeding patterns molecular regulation mechanism in actual production is still unclear. The study aimed to explore the most suitable feeding pattern for Chinese Holstein calves to improve the rumen fermentation function and growth performance of calves. In this regard, the interactions between rumen microorganisms and host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…Prevotella has the highest abundance in the rumen microbial community of ruminants and is closely related to the digestion and metabolism of cellulose, protein, and pectin [ 50 , 51 , 52 , 53 ]. Similar results were observed in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella has the highest abundance in the rumen microbial community of ruminants and is closely related to the digestion and metabolism of cellulose, protein, and pectin [ 50 , 51 , 52 , 53 ]. Similar results were observed in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Their results have revealed that low temperatures prolong the age of silkworms and stabilize acetylcholinesterase activity. Conversely, high temperatures lead to lower disease resistance, higher mortality, and higher acetylcholinesterase activity (Wang, 2011).…”
Section: Introductionmentioning
confidence: 99%